The Polymorphism of the ACE Gene Affects Left Ventricular Hypertrophy and Causes Disturbances in Left Ventricular Systolic/Diastolic Function in Patients with Autosomal Dominant Polycystic Kidney Disease - Maria Wanic-Kossowska; Bartlomiej Posnik; Mikolaj Kobelski; Elzbieta Pawliczak; Krzysztof Pawlaczyk; Krzysztof Hoppe; Krzysztof Schwermer; Dorota Sikorska (The Scientific World Journal)
Autosomal dominant polycystic kidney disease (ADPKD) is one of the most frequently occurring autosomal diseases inherited in the dominant manner. Due to this, lesions in the cardiovascular system of ADPKD patients have caught the attention of clinical investigators worldwide. The aim of the study was to analyse cardiovascular complications in ADPKD patients with a focus on left ventricular hypertrophy (LVH) and selected components of its systolic/diastolic function based on echocardiography. The study was conducted on 55 patients with ADPKD (24 males, 31 females), subdivided into three groups according to the stage of chronic kidney disease (CKD). The patient group with ADPKD and ESRD (group C) manifested an increased incidence of the D allele as compared to group A and group B (χ2=4.217, P=0.04). In all ADPKD patients with the DD genotype, left ventricular mass (LVM), posterior wall thickness (PWT), and interventricular septal thickness (IVS) were significantly higher compared to patients possessing the II and ID genotypes (P<0.02, P<0.003, and P<0.009, resp.). The DD genotype exists more frequently in ADPKD patients with ESRD and is associated with a higher occurrence of LVH and disturbances in systolic-diastolic function when compared to ADPKD ESRD patients with the II and ID genotypes.